Sunitinib and Evofosfamide (TH‐302) in Systemic Treatment‐Naïve Patients with Grade 1/2 Metastatic Pancreatic Neuroendocrine Tumors: The GETNE‐1408 Trial. (14th July 2021) - Grande, Enrique; Rodriguez‐Antona, Cristina; López, Carlos; Alonso‐Gordoa, Teresa; Benavent, Marta; Capdevila, Jaume; Teulé, Alex; Custodio, Ana; Sevilla, Isabel; Hernando, Jorge; Gajate, Pablo; Molina‐Cerrillo, Javier; et al.
Abstract: Background: Sunitinib (SUN)‐induced hypoxia within the tumor could promote the activation of the prodrug evofosfamide (EVO), locally releasing the cytotoxic DNA alkylator bromo‐isophosphoramide mustard. SUNEVO, a phase II, open‐label, single‐arm trial, investigated the potential synergy of SUN plus EVO in advanced progressive pancreatic neuroendocrine tumors (panNETs). Methods: Systemic treatment‐naïve patients with advanced or metastatic, unresectable, grade 1/2 panNETs with a Ki67 ≤20%, received EVO 340 mg/m 2 on days 8, 15, and 22 every 4 weeks and sunitinib 37.5 mg/day continuously. The primary endpoint was objective response rate, measured every 8 weeks by RECIST version 1.1. Results: From 2015 to 2018, 17 patients were enrolled. The median age was 62.4 years, 47% had a Ki67 >10%, and 70.6% had liver metastasis. Patients received a median of five and four cycles of SUN and EVO, respectively. After a median follow‐up of 15.7 months, 17.6% of patients achieved a complete ( n = 1) or partial response ( n = 2), and 11 patients had stable disease (64.7%). The median progression‐free survival was 10.4 months (95% confidence interval, 2.6–18.0). Treatment‐related adverse events (grade ≥3) were observed in 64.7% of the patients, the most frequent being neutropenia (35.3%), fatigue (17.6%), and thrombopenia (11.8%). Treatment discontinuation due to toxicity was reported in 88.2% of the patients. No correlation was found between treatment response and DAXX, ATRX, MEN1, SETD2, and PTEN gene mutations. Conclusion: SUN plus EVO had a negative toxicity profile that should be taken into account for further clinical research in advanced panNETs. The combination showed moderate activity in terms of treatment response that did not correlate with somatic mutations. ( Clinical trial identification number : NCT02402062) Implications for Practice: Addition of hypoxia‐activated prodrugs has been proposed as a potential mechanism to overcome tumor resistance to antiangiogenic agents. Sunitinib and evofosfamide, which were widely proposed as a potential synergistic option, showed modest efficacy in pancreatic neuroendocrine tumors (panNETs), reaching a median objective response rate of 17.6% and median progression‐free survival of 10.4 months. Treatment response does not correlate with the biomarkers analyzed. The high systemic toxicity, with 88.2% of patients discontinuing the treatment, makes this therapeutic approach unfeasible and encourages future research to overcome panNETs' resistance to antiangiogenic agents with other therapies with a safer profile. Abstract : The SUNEVO trial pursued the hypothesis that the hypoxia induced by sunitinib might foster the activation of the prodrug evofosfamide in patients with locally advanced or metastatic pancreatic neuroendocrine tumors. Results are reported here.